The correlation between the neutrophil-to-lymphocyte ratio and the stage of acute kidney injury based on akin criteria in patients hospitalized - Bustani, Bintang; Gunawan, Yusuf Adi; Karita, Dewi; Susiyadi, Susiyadi (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Over the past few decades, the incidence of patients experiencing acute kidney injury (AKI) has increased, necessitating inpatient care. The prognosis of AKI patients is influenced by the management they receive, requiring swift and accurate intervention to prevent poor outcomes. Current AKI diagnostic biomarkers are considered slow, affecting the timeliness of treatment. This study aims to investigate the correlation between the neutrophil-to-lymphocyte ratio (NLR) and AKI as an early biomarker that has the potential to predict AKI. Objective: This study aims to determine whether there is a correlation between NLR and the stage of AKI using the AKIN criteria and the NLR cutoff for each stage of AKI. Methods: This study is a cross-sectional study. Subjects were selected using consecutive sampling. Data were collected using secondary data from the medical records of PKU Muhammadiyah Purbalingga Hospital. Results: We conducted 101 study subjects, there were 49 male and 52 female, with an average age of 62.3 years. Cardiovascular comorbidities were the most common among AKI patients, with 44 subjects affected. A significant correlation was found between NLR and the stage of AKI, as follows: a statistical analysis using ordinal logistic regression (p=0.044), odds ratio (1.03), and multivariate AUC test (77%), cut off (17.7) with specificity (71%) and sensitivity (75%). Conclusion: There is a correlation between NLR and the stage of AKI using AKIN criteria at PKU Muhammadiyah Purbalingga Hospital.